9. a) 8(9 – 2x) = 5(2 – 3x);
B)2(x – 3) = 3(2x - 1);​

vanchugovp02hjd vanchugovp02hjd    3   01.04.2020 16:08    0

Ответы
LansWensEEe LansWensEEe  12.10.2020 11:52

а)72 - 16х = 10 - 15х

-х = -62

х = 62

б)2х - 6 = 6х - 3

2х - 6х = -3 + 6

-4х = 3

х = - 3 / 4

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Элла03 Элла03  12.10.2020 11:52

Пошаговое объяснение:

8(9 – 2x) = 5(2 – 3x)

72-16x=10-15x

16x-15x=72-10

x=62

ответ: 62.

2(x – 3) = 3(2x - 1)

2x-6=6x-3

6x-2x=3-6

x=-3/4

ответ: -3/4.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика